Deoxyribonucleotide Pools and Deoxyribonucleic Acid Synthesis in Mouse Embryo Cells Infected with Three Classes of Polyoma Virus Particles - Skoog, Lambert (1970)
Polyoma virus particles were purified by equilibrium centrifugation in CsCl. Particles from three regions of the density gradient were examined for infectivity, for their ability to induce expanded pools of deoxyribonucleic acid (DNA) precursors, and for their ability to stimulate the synthesis of DNA. The most infectious population of particles, the virions, having a buoyant density of 1.33 g/ml, gave the greatest stimulation of the DNA-synthesizing apparatus of mouse embryo cells. Empty particles at density 1.29 g/ml had no DNA stimulatory activity. A population of particles of intermediate density, referred to as pseudovirions, was also much less active than virions in stimulating DNA synthesis, and the limited stimulatory activity of the latter fraction may be accounted for by its measured contamination with infective particles.